Good living within social and ecological limits: having too much and damaging nature too much are not separate issues - León, Mauricio (Iberoamerican Journal of Development Studies, 2019)
The objective is to delineate the arguments of a Good Living Limitarianism through the analysis and critique of the doctrine of financial limitarianism —it is not morally permissible to be rich, that is, to have more financial resources than those necessary for a fully flourishing life—. The financial limitarianism’s political equality argument is extended to include the rights of ethnic minorities, and the argument of the social justice is extended to include the reduction of social inequality and the Good Living’s community principle. The argument of ecological sustainability is added based on the Good Living’s principle of sufficiency. It is concluded that a Good Living Limitarianism must simultaneously consider the social limits to wealth formulated by limitarianism and the ecological limits imposed by a full and harmonious life with nature: having or not having too much and damaging or not damaging ecosystems too much are not separate issues.